The Influence of Motivation on Quality Service Delivery in Decentralised Indonesia - Eddy Soeryanto Soegoto (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2017)
In this study, the authors sought to examine the relationship between motivation and quality service delivery in a decentralised Indonesia. In an effort to have fair findings, a sample of the study was obtained from 102 local government service delivery recipients. The selected samples included department heads whose sectors became units of inquiry and analysis. During the data collection process, questionnaires were used and data analysis entailed running correlationsand regressing motivation practices on quality service delivery. The results have shown that motivational practices positively and significantly predict quality service delivery in a decentralised Indonesia. Besides, the results also revealed that motivation positively and significantly influences quality service delivery in districts found in the West Java Province,especially, Bandung city.